Offline Location Tracking Service and Image Capturing System Using Android Mobile - JasmineJinitha, A; Rexline, SJ; JasmineSugil, A (International Journal of Computer Sciences and Engineering, 2025)
A smart phone is one of the widely used electronic device and it is the pivot of all smart systems. In this paper we focused to find the stolen or lost android device and provide security to the data stored. The proposed system use a siren sound, when victim try to use the android device by putting wrong password at most three attempts and the background application of camera will automatically runs and capture victims face immediately. Here we use one central web data storage andthe mail id to retrieve whole device data where it will already have uploaded. The proposed system use a novel method called Location-Based Delivery (LBD) which combines the Short Message Service(SMS) and Global Positioning System (GPS) and further a realistic system for tracking a target movement is developed. The proposed approach LBD, consists of three primary types: Short message layout, location prediction, and dynamic threshold. Location is predicted using the current location, moving speed, and bearing of the target to calculate its next location. When the distance between the predicted location and the actual location exceeds a definite threshold, the target transmits a short message to the tracker to update its current location. To maintain the location tracking correctness and the number of short messages on the basis of the moving speed of the target, the threshold is vigorously adjusted.